Exploring near-border territories of Russia: peculiarities of ethnic identity of population - Irina N. Molodikova, Olga L. Sytykh, Svetlana G. Maximova,Daria A. Omelchenko Oksana E. Noyanzina, (Opción, 2019)
This article describes the results of exploring ethnic identity of population, residing in border regions of Russia. As a method, a binary regression model was built to evaluate the probability of inclusion in the group with apparent ethnic identity, which had been measured by means of one statement from cognitive component. In result, the model has confirmed the close relationship between different parts and manifestations of the ethnic identity. As a conclusion, the boundary area needs special approach to the management in the interethnic sphere and diversification of national strategies, taking into account all facets of ethno-cultural life.